Prospective associations between measures of gross and fine motor coordination in infants and objectively measured physical activity and sedentary behavior in childhood. Issue 46 (November 2017) - Sánchez, Guillermo F López; Williams, Genevieve; Aggio, Daniel; Vicinanza, Domenico; Stubbs, Brendon; Kerr, Catherine; Johnstone, James; Roberts, Justine; Smith, Lee
Abstract : Abstract: One important determinant of childhood physical activity and sedentary behavior may be that of motor development in infancy. The present analyses aimed to investigate whether gross and fine motor delays in infants were associated with objective and self-reported activity in childhood. Data were from the UK Millennium Cohort Study, a prospective cohort study, involving UK children born on or around the millennium (September 2000 and January 2002). When children were 9 months old, parents reported children's fine and gross motor-coordination, and at 7 years, sports club attendance and daily TV viewing time. Children's physical activity was measured using accelerometers at 7 years. Adjusted regression models were used to examine associations between delayed motor development and accelerometry measured moderate-to-vigorous physical activity and sedentary behavior, and parent-reported sport club attendance and TV viewing time. In this sample (n = 13, 021), gross motor delay in infancy was associated with less time in moderate-to-vigorous physical activity (B −5.0 95% confidence interval [CI] −6.8, −3.2) and more time sedentary (B 13.5 95% CI 9.3, 17.8) in childhood. Gross and fine motor delays during infancy were associated with a reduced risk of having high attendance at sports clubs in childhood (both relative risk [RR] 0.7, 95% CI 0.6, 0.9). Fine motor delays, but not gross delays, were also associated with an increased risk of having high TV viewing time (RR 1.3 95% CI 1.0, 1.6). Findings from the present study suggest that delays in motor development in infancy are associated with physical activity and sedentary time in childhood. Abstract : Supplemental Digital Content is available in the text